Perfect Simple in Wallachia and Transylvania: A Typological Approach - Mădălina Chitez (Linguaculture, 2010)
The focus of the article is the dialectal-typological analysis of Perfect Simple/PS (Ro. ‘perfectul simplu’) in Romanian dialects, i.e. Bobiceşti/Olt/Wallachia and Almaş/Arad/Transylvania. Paralleled by the main literature-based characteristics of the tense, the data do not only emphasize the surprisingly preponderant distribution of PS in Transylvania but they also reveal the key status of the Perfect Simple as part of the Romanian dialect use as well as its typologically relevant double status (Standard Romanian versus dialect use). The comparison between the ‘general purpose’ Latin-to- Romance PS evolution and the ‘Balkansprachbund’ Greek-Aorist characteristics ends with commentaries on the double perspective of Romanian: Wallachian (generally reflected in Standard Romanian) manifests Balkan-oriented phenomena and Transylvanian preserves Latin/Romance-oriented features.